Respuesta :
distribute
a(b+c)=ab+ac
3p(3pq-4)=9p^2q-12p
we have
3p^2q+9p^2q-12p+5p^3
add like terms
4p^3+12p^2q-12p
a(b+c)=ab+ac
3p(3pq-4)=9p^2q-12p
we have
3p^2q+9p^2q-12p+5p^3
add like terms
4p^3+12p^2q-12p
Step by Step
3p^2q+3p(2pq−4)+5p^3
Distribute:
=3p^2q+(3p)(2pq)+(3p)(−4)+5p^3=3p2q+6p2q+−12p+5p3
Combine Like Terms:
=3p^2q+6p^2q+−12p+5p^3=(5p^3)+(3p^2q+6p^2q)+(−12p)=5p^3+9p^2q+−12p
=5p^3+9p^2q−12p
3p^2q+3p(2pq−4)+5p^3
Distribute:
=3p^2q+(3p)(2pq)+(3p)(−4)+5p^3=3p2q+6p2q+−12p+5p3
Combine Like Terms:
=3p^2q+6p^2q+−12p+5p^3=(5p^3)+(3p^2q+6p^2q)+(−12p)=5p^3+9p^2q+−12p
=5p^3+9p^2q−12p